Recent progress on stability and thermo-physical properties of mono and hybrid towards green nanofluids - Zainon, S. N. M.; Azmi, W. H. (MDPI AG, 2021)
Many studies have shown the remarkable enhancement of thermo-physical properties with the addition of a small quantity of nanoparticles into conventional fluids. However, the long-term stability of the nanofluids, which plays a significant role in enhancing these properties, is hard to achieve, thus limiting the performance of the heat transfer fluids in practical applications. The present paper attempts to highlight various approaches used by researchers in improving and evaluating the stability of thermal fluids and thoroughly explores various factors that contribute to the enhancement of the thermo-physical properties of mono, hybrid, and green nanofluids. There are various methods to maintain the stability of nanofluids, but this paper particularly focuses on the sonication process, pH modification, and the use of surfactant. In addition, the common techniques to evaluate the stability of nanofluids are undertaken by using visual observation, TEM, FESEM, XRD, zeta potential analysis, and UV-Vis spectroscopy. Prior investigations revealed that the type of nanoparticle, particle volume concentration, size and shape of particles, temperature, and base fluids highly influence the thermo-physical properties of nanofluids. In conclusion, this paper summarized the findings and strategies to enhance the stability and factors affecting the thermal conductivity and dynamic viscosity of mono and hybrid of nanofluids towards green nanofluids.